A review on: Biodiversity and Ecological Significance of Wild Legumes in the Western Ghats - Landage K. B; Nikam T. D.; Naikawadi V. B. (The Bioscan, 2025)
This review summarizes the diversity, ecological roles, ethnobotanical relevance, conservation status, and microbiological associations of wild legume (Fabaceae) species in the Western Ghats, one of the world’s most important biodiversity hotspots. Wild legumes contribute significantly to ecosystem functioning through nitrogen fixation, soil fertility enhancement, carbon sequestration, and habitat stabilization. Many species hold traditional medicinal, nutritional, and cultural value among local and Indigenous communities, reflecting their ethnobotanical importance. The review also highlights the symbiotic interactions of these legumes with rhizobia and non-rhizobial endophytes, emphasizing their potential in sustainable agriculture, biofertilizer development, and ecosystem restoration. Emerging biotechnological approaches including microbial inoculant formulation, phytochemical exploration, and genetic characterization offer new opportunities to harness the functional diversity of these species. Despite their ecological and economic importance, numerous wild legumes face threats from habitat loss, overharvesting, and climate change, underscoring the need for targeted conservation strategies. This review integrates current research to provide a comprehensive understanding of wild legume resources in the Western Ghats and proposes future directions for conservation, sustainable utilization, and biotechnological innovation.